Uterine leucocyte infiltration after artificial insemination in bitches - Coelho Ribeiro, Ana Paula; Russiano Vicente, Wilter Ricardo; Apparicio, Maricy; Figueiredo Gadelha, Carla Renata; Alves, Aracelle Elisane; Covizzi, Gabriela Jayme (Elsevier B.V., 2006)
In the present study, polymorphonuclear neutrophils (PMN) were enumerated to evaluate acute uterine inflammation after artificial insemination in the bitch. It was concluded that the canine seminal plasma possessed an immunomodulating action. However, the most commonly used extender for freezing canine semen (Tris glucose with egg yolk and glycerol) was a potential inducer of uterine inflammation. (c) 2006 Published by Elsevier B.V.
Keywords: uterine inflammation; artificial insemination; bitch; canine